Foreword - Bonnefoit, Régine; Rérat, Melissa; Samuel Schellenberg (My University, 2023)
The history of art and new media are inextricably linked — both historically and in the present day. This publication can be described as an interdisciplinary reflection: it examines the confrontation and inter action between art history and new media, highlighting key developments, opportunities, and tensions. In eight studies, eleven researchers present new findings and explore the techniques and methods of new media — from electronic to digital and post digital media — and the challenges these pose for art history. The book covers a wide range of topics, from the history and historiography of new media to their practical application, use, and reception, as well as creative processes, material conservation, and mediation.
Publication of the colloquium: ART HISTORY AND NEW MEDIA: WHAT’S UP? SITUATION AND PROSPECTS, 15 - 16th. OCTOBER 2021, HEK HAUS (HAUS DER ELEKTRONISCHEN KÜNSTE), MÜNCHENSTEIN/ BASEL & ONLINE
Keywords: Digital mediation; art history and new media